2013
DOI: 10.1179/0076609713z.00000000015
|View full text |Cite
|
Sign up to set email alerts
|

Engendering Debate: Animals and Identity in Anglo-Saxon England

Abstract: WITH THE GROWING popularity of theoretical approaches within medieval archaeology, identity has become a central area of research. Although such studies frequently expound upon the role of the material world in negotiations between individuals and society, there is a tendency to overlook what were fundamental agents within this process: animals. This is especially true of Anglo-Saxon England, where farming determined the daily experiences of most people and the exchange of animals was fundamental to the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…With few exceptions, this perceived disinterest in gender contrasts with early medieval, Anglo-Saxon and Viking studies, in which these subjects are explored to some extent (e.g. Lucy 2011; Poole 2013; O'Sullivan 2015). Is this indifference a reflection of unconscious bias in scholarly research or a conscious effort to reinforce a particular status quo?…”
Section: Gender and Medieval Archaeology In Britain And Irelandmentioning
confidence: 90%
“…With few exceptions, this perceived disinterest in gender contrasts with early medieval, Anglo-Saxon and Viking studies, in which these subjects are explored to some extent (e.g. Lucy 2011; Poole 2013; O'Sullivan 2015). Is this indifference a reflection of unconscious bias in scholarly research or a conscious effort to reinforce a particular status quo?…”
Section: Gender and Medieval Archaeology In Britain And Irelandmentioning
confidence: 90%
“…2007 , p. 112). The same would have been true of animals in the past as well (Poole 2013a ), with people, whether farmers or not, organising their way of life, landscape and diet according to the animals inside and outside of their care. The question of whether or not animals resist or co-operate with humans due to intentions, instincts or a combination of the two is a difficult one to answer.…”
Section: Animals As Agentsmentioning
confidence: 97%
“…However, such information can also reveal a considerable amount concerning their contact with humans in life. Given their central role in creating social worlds, these interactions were at least as important as the end result (Poole 2013a , b ). Reconstructing past human–animal relationships is not without its challenges, as some species may be less frequently recovered in excavations.…”
Section: Anglo-saxon England and The Physical Remains Of Catsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of Anglo-Saxon literature and the material culture of burials have also revealed the role of consumption (particularly of drink) in mediating social relationships of power and status in the period (Magennis 1999). In a similar vein, Kristopher Poole (2013) has demonstrated that relationships with animals, including their consumption as food, contributed to the establishment of gendered and status based identities in Anglo-Saxon England. Archaeological research examining cuisine in later periods has demonstrated there to be a changing relationship between animal exploitation and status in the medieval period, which can be linked to a range of social and economic factors, such as the need for secondary products and the rituals associated with hunting (Albarella 2005;Sykes 2006a;Thomas 2006), whilst the exploitation of spices and exotic plant foodstuffs has been shown to relate to urbanisation and social stratification across north-western Europe (Groenmanvan Waateringe 1994;Karg 2007;Livarda 2011;Livarda and Van der Veen 2008).…”
mentioning
confidence: 96%